1975
DOI: 10.1111/j.1752-1688.1975.tb00681.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF SELECTED HERBICIDES ON BACTERIAL POPULATIONS IN NONTREATED AND TREATED WATER1

Abstract: Bacterial populations in nontreated and herbicide‐treated waters were subjected to three different herbicides. Diuron, dichlobenil, and diquat were added (100 mg/l) to water samples from two fresh water lakes and two herbicide‐treated ponds. Total numbers of bacteria were monitored. Bacterial populations in fresh lake water decreased after herbicide additions; however, final populations were significantly greater than the controls. Similar observations were recorded for bacteria in dichlobenil‐ and diuron‐trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1980
1980
1982
1982

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Since the data show such a large degree of difference in the affects that the herbicides have on the oxygen depletion between the base concentration and ten times this value, it is sug- gested that further studies be completed to assess the herbicides' effect in this intermediate range. These results are similar to those found by Van Schreven et al (1970) and Yazar et al (1975) who found a stimulation of bacterial growth was associated with the addition of a herbicide.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Since the data show such a large degree of difference in the affects that the herbicides have on the oxygen depletion between the base concentration and ten times this value, it is sug- gested that further studies be completed to assess the herbicides' effect in this intermediate range. These results are similar to those found by Van Schreven et al (1970) and Yazar et al (1975) who found a stimulation of bacterial growth was associated with the addition of a herbicide.…”
Section: Methodssupporting
confidence: 92%
“…Torgeson (1971) reported on bacteria grown under anaerobic conditions and found that grampositive cocci and gram-positive rods were not affected by the herbicide DCPA, while gram-negative rods did not grow. In lake water treated with the herbicides diuron, dichlobenil and diquat, a stimulating effect on bacterial growth was observed by Yazar et al (1975). The bacterial populations in the treated samples indicated an extended lag period and a higher population decrease than the control samples.…”
Section: Review Of Literaturementioning
confidence: 95%
“…Comparison of levels of fecal coliforms in feeder streams and reservoirs shows that feeder stream concentrations were generally tenfold higher than the reservoir concentrations. During early spring dry periods, fecal contamination introduced from the feeder creeks was diluted in the impoundment through sedimentation and dispersion to a concentration of approximately 10 percent of initial values. However, stormwater runoff discharged into the small reservoir temporarily reversed the reduction of organisms, and reservoir fecal coliform densities temporarily increased by about 1 log.…”
Section: *Nucleporementioning
confidence: 99%